COMPARATIVE EVALUATION OF ARTIFICIAL INTELLIGENCE AND MEDICAL STUDENTS IN MEDICAL KNOWLEDGE ASSESSMENT: INSIGHTS FOR ENHANCING MEDICAL EDUCATION - Bakhodir B. Rakhimov; Erkin Yo. Sultonov; Dilafruz A. Turabayeva; Sabina K. Sodikova; Fatima Z. Alimova (Central Asian Journal of Medicine, 2024)
This study aims to compare the effectiveness of artificial intelligence (AI) tools, specifically ChatGPT and Bing, with that of local and international medical students in understanding and responding to medical questions. The goal is to evaluate the potential role of AI in medical education and identify knowledge gaps among different student groups. The study highlights the potential of AI tools to supplement medical education by providing accurate information and aiding in learning.